KONTRIBUSI SELF-REGULATED LEARNING TERHADAP KEPUASAN MAHASISWA MENGENAI PEMBELAJARAN JARAK JAUH YANG DIMODERASI PENILAIAN PERAN PENGAJAR - Amaliyah Nur Azizah, - (2021)
Penelitian ini memiliki tujuan untuk melihat kontribusi self-regulated learning terhadap kepuasan mahasiswa yang dimoderasi penilaian peran pengajar dalam pembelajaran jarak jauh. Responden (N=337) mahasiswa angkatan 2016, 2017, 2018, 2019 Universitas Pendidikan Indonesia mengisi Online Self-Regulated Learning Questionnaire (OSLQ) untuk mengukur self-regulated learning mahasiswa dalam PJJ, instrumen student satisfaction with online learning untuk mengukur kepuasan mahasiswa selama menjalani pembelajaran jarak jauh, dan Scale of Teacher Role Inventory (STRI) untuk mengukur penilaian mahasiswa terhadap peran pengajarnya. Teknik sampel yang digunakan adalah teknik incidental sampling. Teknik analisis data yang digunakan adalah analisis regresi linear untuk mengetahui kontribusi self-regulated learning terhadap kepuasan mahasiswa dan regresi berganda untuk mengetahui kontribusi self-regulated learning terhadap kepuasan mahasiswa yang dimoderasi peran pengajar dalam pembelajaran jarak jauh. Hasil penelitian ini menunjukkan bahwa peran pengajar memoderasi kontribusi self-regulated learning terhadap kepuasan mahasiswa dalam pembelajaran jarak jauh. Kata kunci: self-regulated learning, kepuasan mahasiswa, peran pengajar, mahasiswa, PJJ. Amaliyah Nur Azizah (1600276). Contribution of Self-Regulated Learning to Student Satisfaction with Teachers' Roles Moderation in Distance Learning. Thesis. Departement of Psychology, Faculty of Education, Indonesia University of Education. Bandung. (2021). This study aims to examine the contribution of self-regulated learning to student satisfaction moderated by the teachers' roles in distance learning. Respondents (N = 337) college students generation 2016-2019 in Indonesia University of Education filled out the Online Self-Regulated Learning Questionnaire (OSLQ) to measure student self-regulated learning in distance learning, student satisfaction with online learning instruments to measure student satisfaction during distance learning, and the Scale of Teacher Role Inventory (STRI) to measure student perceptions of the teachers' roles. The sample technique used is the incidental technique. The data analysis technique used is linear regression analysis to see the contribution of self-regulated learning to student satisfaction and multiple regression to see the contribution of self-regulated learning to student satisfaction moderated by the teachers' roles in distance learning. The results of this study indicate that the teachers' roles moderating the contribution of self-regulated learning to student satisfaction in distance learning. Keywords: self-regulated learning, student satisfaction, teacher's roles, college students, distance learning.